Synthesis and electrocatalytic behavior of cobalt (II)-tris(benzyl-mercapto)-monoaminophthalocyanine–single walled carbon nanotube nanorods - Mugadza, Tawanda; Nyokong, Tebello (Elsevier, 2016)
In this paper we report on synthesis and electrocatalytic behavior of cobalt (II)-tris(benzyl-mercapto)-monoaminophthalocyanine–single walled carbon nanotube nanorods towards the oxidation of amitrole. SWCNTs that were terminally functionalized with carboxylic acid groups were chemically linked to cobalt (II)-tris(benzyl-mercapto) monoaminophthalocyanine (CoMAPc) via an amide bond to form nanorods. UV–vis, FTIR, TEM, Raman and XRD spectroscopies were used in characterization of the nanorods (CoMAPc–SWCNT-linked), while cyclic voltammetry and chronoamperometry were used during the characterization of amitrole on the modified glassy carbon electrode. The linear dynamic range for the amitrole was from 1.0 × 10−6 M to 1.2 × 10−4 M, with a sensitivity of 6.76 A mol−1 L cm−2. The estimated limit of detection for amitrole was 0.10 μM, using the 3δ criterion. The catalytic rate constant was found to be 1.09 × 105 M−1 s−1.